Deviations From the Ideal Plasma Volume and Isolated Tricuspid Valve Surgery—Paving the Way for New Risk Stratification Parameters - Hasimbegovic, Ena; Russo, Marco; Andreas, Martin; Werner, Paul; Coti, Iuliana; Wiedemann, Dominik; Kocher, Alfred; Laufer, Günther; Hofer, Benedikt S.; Mach, Markus (Frontiers in Cardiovascular Medicine, 2022)
Background: Congestion and plasma volume expansion are important features of heart failure, whose prognostic significance has been investigated in a range of surgical and non-surgical settings. The aim of this study was to evaluate the value of the estimated plasma volume status (ePVS) in patients undergoing isolated tricuspid valve surgery. Methods: This study included patients who underwent isolated tricuspid valve surgery at the Vienna General Hospital (Austria) between July 2008 and November 2018. The PVS cut-off was calculated using ROC analysis and Youden’s Index. Results: 88 patients (median age: 58 [IQR: 35-70] years; 44.3% male; 75.6% NYHA III/IV; median EuroSCORE II 2.65 [IQR: 1.70-5.10]; 33.0% endocarditis-related regurgitation; 60.2% isolated repair; 39.8% isolated replacement) were included in this study. Patients who died within one year following surgery had significantly higher baseline ePVS values than survivors (median ePVS 5.29 [IQR: -1.55-13.55] vs. -3.68 [IQR: -10.92-4.22]; p = 0.005). During a median actuarial follow-up of 3.02 (IQR: 0.36 – 6.80) years, patients with a preoperative ePVS ≥ -4.17 had a significantly increased mortality (log-rank p = 0.006). Conclusions: ePVS is an easily obtainable risk parameter for patients undergoing isolated tricuspid valve surgery capable of predicting mid- and long-term outcomes after isolated tricuspid valve surgery.